Annual Plan For 1971-72 Part I-Outline Government of Maharashtra - Planning Commission (Planning Commission, 1971)
The three years, viz., 1965-66 to 1967-68, had been of a great strain to General the State’s economy, due mainly to the severe drought conditions, floods and other situation, natural calamities. However, a distinct improvement in the economic situation was witnessed in 1968-69 and the State was able to overcome to a large extent the effects of strains of past years. These favourable trends more-or-less continued in 1969-70. After two good years, the economy has been somewhat chequered during 1970-71.
Government of Maharashtra, Finance Department (Planning)